Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1073/pnas.82.22.7525
|View full text |Cite
|
Sign up to set email alerts
|

Products of nitrogen regulatory genes ntrA and ntrC of enteric bacteria activate glnA transcription in vitro: evidence that the ntrA product is a sigma factor.

Abstract: In enteric bacteria the products of two nitrogen regulatory genes, ntrA and ntrC, activate transcription of ginA, the structural gene encoding glutamine synthetase, both in vivo and in vitro. The ntrC product (gpntrC) is a DNA-binding protein, which binds to five sites in the ginA promoter-regulatory region and appears to activate transcription initiation.Using as an assay the stimulation of ginA transcription in a coupled in vitro transcription-translation system, we have partially purified the ntrA gene prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
266
0
2

Year Published

1987
1987
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 328 publications
(276 citation statements)
references
References 34 publications
5
266
0
2
Order By: Relevance
“…As judged by DNase I-and methylation-protection assays, the NtrC protein binds to five sites in the glnA promoter region (33) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As judged by DNase I-and methylation-protection assays, the NtrC protein binds to five sites in the glnA promoter region (33) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…a-54, the NtrC activator protein [NtrCcon mutant form = NtrC610 (9)], and NtrB [the kinase that phosphorylates NtrC (32)] were purified as described (33,34 Proteins were first mixed together and then added to the DNA. For the reactions in Table 1, buffer A was used together with NtrC (360 nM) and wild-type DNA fragment (34 nM).…”
mentioning
confidence: 99%
“…It has been demonstrated that Streptomyces, like E. coli (Grossman et al, 1984;Landick et al, 1984), Bacillus (Losick & Pero, 1981) and recently the mntrogen-regulated genes of enteric bacteria (Hirschman et al, 1985) possess multiple sigma (C) factors (Westpheling et al, 1985;Buttner & Brown, 1985) which are each believed to initiate transcription from a specific class of promoter. In S. coelicolor one of the a-factors identified, probably the o.40 found by Buttner & Brown (1985) or o45 of Westpheling et al (1985), may be analogous to the E. coli a`70 factor that recognizes the consensus promoter of TTGACA (-35 region) and TATAAT (-10 region), and may be partly responsible for the capacity of Streptomyces to recognize and initiate transcription from promoters derived from a diverse source of bacteria including E. coli (Bibb & Cohen, 1982;Jaurin & Cohen, 1984;Westpheling et al, 1985;Herbert et al, 1986).…”
Section: Streptomyces Lividansmentioning
confidence: 99%
“…However, the initiation of transcription at specific DNA sequences requires additional protein(s). In bacteria, these additional proteins are called the " factors" (1,2). The factor facilitates transcription at specific DNA sequences by 1) binding to the core RNAP to form the -RNAP holoenzyme, 2) recognizing and binding to a specific DNA sequence next to the transcription start site, called the promoter element, and 3) opening the double-stranded DNA to initiate transcription.…”
mentioning
confidence: 99%
“…The primary protein complex catalyzing transcription is composed of five subunits, ␣ 2 ␤Ј␤, called "core RNA polymerase" (RNAP). 2 Core RNAP is fully competent to synthesize RNA from DNA. However, the initiation of transcription at specific DNA sequences requires additional protein(s).…”
mentioning
confidence: 99%